2004
DOI: 10.1167/iovs.03-1145
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Dry Eye Stimulates Production of Inflammatory Cytokines and MMP-9 and Activates MAPK Signaling Pathways on the Ocular Surface

Abstract: Experimental dry eye stimulates expression and production of IL-1beta, TNF-alpha, and MMP-9 and activates MAPK signaling pathways on the ocular surface. MAPKs are known to stimulate the production of inflammatory cytokines and MMPs, and they could play an important role in the induction of these factors that have been implicated in the pathogenesis of dry eye disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
386
1
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 512 publications
(412 citation statements)
references
References 44 publications
17
386
1
8
Order By: Relevance
“…18 Previous studies showed that inflammatory cytokines including IL-1, IL-6, IL-8, and TNF-a, are important mediators in both human and animal DEDs. [19][20][21][22] Recent reports indicated that pro-inflammatory cytokines were significantly increased in the conjunctiva tissue and tears of NSSDE and SSDE patients. 21,22 Th17 cells are the newly recognized CD4 þ T-cell subset, which mainly produces cytokines, including IL-17A, IL-17F, and IL-22, and is involved in a wide range of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Previous studies showed that inflammatory cytokines including IL-1, IL-6, IL-8, and TNF-a, are important mediators in both human and animal DEDs. [19][20][21][22] Recent reports indicated that pro-inflammatory cytokines were significantly increased in the conjunctiva tissue and tears of NSSDE and SSDE patients. 21,22 Th17 cells are the newly recognized CD4 þ T-cell subset, which mainly produces cytokines, including IL-17A, IL-17F, and IL-22, and is involved in a wide range of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Recent reports indicated that pro-inflammatory cytokines were significantly increased in the conjunctiva tissue and tears of NSSDE and SSDE patients. 21,22 Th17 cells are the newly recognized CD4 þ T-cell subset, which mainly produces cytokines, including IL-17A, IL-17F, and IL-22, and is involved in a wide range of autoimmune diseases. [11][12][13] The level of IL-17 was found to be correlated with both activity and severity of various autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with experimental models of DED, where both the conjunctiva and cornea were inflamed because of local production of inflammatory cytokines, such as interleukin-1β), tumor necrosis factor-α, and matrix metalloproteinase-9. 41 We speculate that the improved symptoms in MGD patients who had been treated with doxycycline and/or corticosteroids were in part due to the reduction in palpebral conjunctival epithelial immune cells, not made possible with mechanical and thermal gland expression procedures alone. Our speculation is supported by the highly significant correlation between EIC and OSDI found in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Higher levels of dye uptake in the same punctate pattern are associated with dry eye syndrome [129,132,133].…”
Section: Ocular Surface Barrier Function In Dry Eye Diseasementioning
confidence: 97%
“…Elevated gelatinolytic activity was detected within the ocular surface epithelia by in situ zymography [132].…”
Section: Ocular Surface Barrier Function In Dry Eye Diseasementioning
confidence: 99%